MINYAK ESENSIAL SEBAGAI SEBAGAI SALAH SATU PENGOBATAN TERHADAP PENYAKIT KULIT AKIBAT BAKTERI - Lazulfa Inda Lestari (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Skin infections are one of the five most common reasons for someone to seek medical treatment and are considered as the most common infections. In addition, skin diseases are a major cause of mortality and morbidity. Antibiotics have been widely used to fight bacterial infections. But now, bacteria have developed resistance to many antibiotics commonly used to treat infections. An alternative therapy that is being developed for treatment against bacterial skin diseases is the use of essential oils. For centuries, essential oils have been used in aromatherapy and topical uses, such as soap for routine washing and antiseptics for wound healing. The antibacterial properties of essential oils have been shown to be effective against infectious diseases. One example is Melaleuca alternifolia (tea tree), rich in terpinen-4-ol, showing an important activity in antimicrobials. Styrax benzoin, and Cinnamomum zeylanicum (cinnamon), each rich in eugenol, were found to have important activity in antimicrobials